2013
DOI: 10.1590/s1516-18462013005000021
|View full text |Cite
|
Sign up to set email alerts
|

Exposição ao ruído na indústria de transformação no Brasil

Abstract: A exposição ao ruído no trabalho é o fator de risco modificável mais importante para a perda auditiva em adultos. Na indústria de transformação, a exposição a níveis elevados de pressão sonora afeta um grande número de trabalhadores. As normas brasileiras estabelecem como obrigatório, para todas as empresas, o monitoramento do ruído ocupacional e da condição auditiva dos trabalhadores, assim como garantias para a proteção do trabalhador. No entanto, a aplicação das normas é frágil e pouco se sabe sobre a distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
7
0
9
Order By: Relevance
“…Another study also found more cases in the manufacturing sector, being a predominant sector in Brazil, which has the highest rates of hearing problems due to the work process and machinery with high noise levels (26)(27)(28) . This study clarified claims by PHC professionals as to the difficulty in NIHL identification and notification in the city of Curitiba.…”
Section: Discussionmentioning
confidence: 92%
“…Another study also found more cases in the manufacturing sector, being a predominant sector in Brazil, which has the highest rates of hearing problems due to the work process and machinery with high noise levels (26)(27)(28) . This study clarified claims by PHC professionals as to the difficulty in NIHL identification and notification in the city of Curitiba.…”
Section: Discussionmentioning
confidence: 92%
“…Excessively noisy environment, with sound pressure level above 85 dB, without any safety measures for the exposed workers to it, may impair the auditory pathways to the central nervous system (25) . The potentially harmful effects of noise to health, particularly to hearing health, stress the need of investment in management, actions and ongoing process of assessing Hearing Loss Prevention Programs in companies and other workplaces (26) .…”
Section: Discussionmentioning
confidence: 99%
“…The diverse nature of plant equipment used by the manufacturing sector results in variance in emitted noise levels due to the age of the plant equipment, wear and tear of the equipment and operating speed of the operated machines, amongst other factors [22]. The emitted noise levels expose a great percentage of the workforce employed in the sector [23]. Table 1 shows the reported average noise levels in literature, with references, within the manufacturing sector inclusive of the chemical manufacturing industry.…”
Section: Noise Levels In the Manufacturing Sectormentioning
confidence: 99%